2000
DOI: 10.1101/gad.182100
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bak in UV-induced apoptosis in skin cancer and abrogation by HPV E6 proteins

Abstract: Ultraviolet B (UVB) damage is recognized as the most important etiological factor in the development of skin cancer. Human papillomaviruses (HPV) have also been implicated in the disease, although the mechanism of action of these viruses remains unknown. We present evidence here that Bak protein is involved in signaling apoptosis in the skin in response to UVB damage, and that cutaneous HPV E6 proteins target and abrogate Bak function by promoting its proteolytic degradation both in vitro and in regenerated ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
225
2
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(245 citation statements)
references
References 33 publications
10
225
2
8
Order By: Relevance
“…The apoptotic response has been extensively studied because elimination of DNA damaged KCs is an efficient and powerful protective mechanism for preventing development of skin cancer (Ziegler et al, 1994). While UV-light exposure triggers an assortment of cellular alterations involving multiple signaling pathways, dissection of the apoptotic response revealed it is principally mediated by mitochondrial dysfunction (Jackson et al, 2000;Nickoloff et al, 2002;Bowden, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The apoptotic response has been extensively studied because elimination of DNA damaged KCs is an efficient and powerful protective mechanism for preventing development of skin cancer (Ziegler et al, 1994). While UV-light exposure triggers an assortment of cellular alterations involving multiple signaling pathways, dissection of the apoptotic response revealed it is principally mediated by mitochondrial dysfunction (Jackson et al, 2000;Nickoloff et al, 2002;Bowden, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The beta HPV types were first isolated in skin cancer-prone patients suffering from a rare autosomal recessive genetic disorder called epidermodysplasia verruciformis, but it is now clear that they are commonly found in the skin of healthy individuals (Pfister, 2003). Characterization of the biological properties of the products of the early genes E6 and E7 from different beta HPV types in in vitro and in vivo model has highlighted the potential carcinogenicity of these viruses (Jackson et al, 2000;Caldeira et al, 2003;Akgul et al, 2005;Dong et al, 2005;Schaper et al, 2005;Accardi et al, 2006;Michel et al, 2006). We showed that expression of E6 and E7 from the beta HPV38 in primary human keratinocytes results in inactivation of the tumour suppressor p53 and pRb and immortalization (Caldeira et al, 2003;Accardi et al, 2006).…”
mentioning
confidence: 99%
“…Bax mutations have been detected in leukemias, gastrointestinal and colorectal cancer (Rampino et al, 1997;Zhang et al, 2000). Abrogation in Bax and Bak protein expression has been observed in skin, gastric and colorectal cancer (Rosen et al, 1998;Jackson et al, 2000). Deregulation in the p53 pathway seems to be an important target in the development of colorectal cancer, and it is of great interest to investigate whether mutations in Noxa are present in colorectal cancer, and whether the levels of mRNA and protein expression are of importance.…”
mentioning
confidence: 99%